Corporate public affairs : interacting with interest groups, media, and government - Lerbinger, Otto (LEA's communication series., 2006)
Exploring the increasing interest in public affairs by organizations, the author indicates that more and more frequently corporations are establishing public affairs positions - typically within public relations departments - to respond to issues and concerns arising out of the sociopolitical environment in which the corporation functions.